SMART AGRICULTURE IN LAM DONG PROVINCE - Sơn, Thanh Tùng (Nhà xuất bản Tài chính, 2023)
Smart urban agriculture is becoming a trend in the urban development process of many countries, including Vietnam. The research and application of smart and sustainable urban agriculture taking advantage of the results of the industrial revolution 4.0, is becoming more and more popular, which is of great significance in order to improve productivity and efficiency in agriculture. Through the collection, synthesis and analysis of data collected from reports of departments and agencies, research reports in Lam Dong province, this article focuses on describing the current situation of smart agriculture model or, in other words, agriculture with science and technology application in recent years in Lam Dong province. At the same time, the authors also analyze challenges in developing this model as well as present some typical smart agricultural models to help local governments in the Southeast region to draw on experiences when developing smart (urban) agricultural models in the locality.